ҚАРАҚАЛПАҚ ӘДЕБИЯТЫНДА МАГИЯЛЫҚ РЕАЛИЗМ ЭЛЕМЕНТЛЕРИ - Ешниязова, Э.Н. (ILIM hám JÁMIYET, 2026)
This article examines the emergence of elements of magical realism in Karakalpak literature, which is considered one of the directions of the artistic method of realism, which is of great importance in the development of world literature.